Machine Tools Design, Research, Application - Šooš, Ľubomír; Marek, Jiri (IntechOpen, 2020)
Successful producers of machine tools today must offer customers highly efficient and accurate machines. This can only be achieved with the help of modern software in research, construction, production and quality control. Trends in development are oriented towards modular construction machines. The application of modern tools and the progressive construction of headstock has increased cutting speeds, thus significantly increasing the machine's productivity. The first section of the book is focused on trends in the development of machines. A second very significant machine parameter is accuracy. The rigidity of the machine is a necessary condition for achieving its required accuracy. The second part of the book is dedicated to the effect of the individual constructional nodes on stability, the optimization of system rigidity, and the measuring of the accuracy of the machining tools. The aim of the third and final section of the book is to point out the widest possibilities for the application of machine tools in industry. An example is presented of the application of machining tools in the orthoses manufacture.